Russian Empire's military reforms of the second part of the XIX century in modern historiography - Шаравара Т. (Київський національний університет імені Тараса Шевченка, 2010)
It was analyzed the condition of the interpretation military reforms in land forces and navy of the second part of the ХІХ century in the works of modern historians and professional military men. It is appreciated the factors which have an influence on the character and content of the publications, it is indicated the little-studied questions.

Проаналізовано стан висвітлення воєнних реформ сухопутних сил і воєнно-морського флоту другої половини ХІХ ст. у працях сучасних істориків та професійних військових. Оцінено чинники, що вплинули на характер і зміст публікацій, окреслено маловивчені проблеми.
Сучасна історіографія воєнних реформ Російської імперії другої половини ХІХ століття